1989
DOI: 10.1136/jcp.42.8.805
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary embolism at necropsy in patients with cancer.

Abstract: The series studied comprised 6197 patients who had died of or who had cancer at death and represents all patients with cancer from 21,530 necropsies performed at this department from 1960-84. Pulmonary embolism was significantly more common among cancer patients than in those with non-neoplastic diseases. Among those palliatively treated, patients with ovarian cancer, cancer of the extrahepatic bile duct system, and cancer of the stomach had the highest prevalence of pulmonary embolism (34.6%, 31.7%, and 15.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 18 publications
1
55
0
3
Order By: Relevance
“…A study of 21530 Swedish autopsies over a 24-year period showed the highest prevalence of pulmonary embolism was in patients with ovarian cancer, cancer of the extra-hepatic bile duct system and cancer of the stomach. 25 Similar figures emerged from an Italian autopsy study of 27 410 patients. 26 There are significant variations in VTE incidence according to the site of the cancer, whereas associations with disease extension are less convincing.…”
Section: Thromboprophylaxis In Cancer Patientssupporting
confidence: 69%
“…A study of 21530 Swedish autopsies over a 24-year period showed the highest prevalence of pulmonary embolism was in patients with ovarian cancer, cancer of the extra-hepatic bile duct system and cancer of the stomach. 25 Similar figures emerged from an Italian autopsy study of 27 410 patients. 26 There are significant variations in VTE incidence according to the site of the cancer, whereas associations with disease extension are less convincing.…”
Section: Thromboprophylaxis In Cancer Patientssupporting
confidence: 69%
“…4,5 Autopsy studies have reported that patients with cancers involving organs of the abdominal cavity, particularly ovarian, biliary, or stomach cancer, have a high prevalence of pulmonary embolism at the time of death. 6 No population-based study, to our knowledge, has determined the incidence of thromboembolism among patients diagnosed with specific types and stages of cancer.…”
Section: A L T H O U G H C a N C E R I Smentioning
confidence: 99%
“…A study of 21,530 Swedish autopsies [5]over a 24-year period showed the highest prevalence of pulmonary embolism (PE) in patients with ovarian cancer, cancer of the extrahepatic bile duct system and cancer of the stomach (34.6, 31.7 and 15.2%, respectively). Patients with cancer of the oesophagus and larynx, leukaemia, myelomatosis and malignant lymphoma had the lowest prevalence (0–5.6%).…”
Section: Risk Of Vte In Cancermentioning
confidence: 99%